Design and implementation of an optimal fuzzy logic controller using egentic algorithm - Abdulazeez, Salami Femi; Adetunji, Lawal Wahab; Khan, Sheroz; Alam, A. H. M. Zahirul; Salami, Momoh Jimoh Emiyoka; Hameed, Shihab A.; Hassan Abdalla Hashim, Aisha; Islam, Md. Rafiqul (IIUM Press, 2011)
Most control systems suITer from problems related to undesirable overshoot, longer settling times aoo vibrations while going from one state 10 an(){her state. Works so far reponed techniques which are on how to oveTCQme or reduce the effects of these issues for ensuring smoother and finely tuned eolltrolling proceM. The devised solution is softwllrebased which employs an algorithmic approach for programming II PICI6F877A microcontroller, thus eliminating allogether the parametric dependence issues while adding the benefits of easier modification to suit a given control system for varying operational conditions_ The approach is first simulated using MATLAB/and the simulated results are verified by programming {he PICI6I'g77A mierocontrolter with {he algorithm and using it on a temperature control system where a fan is regulated in response to variations in the ambient system temperature. The results justify the effectiveness of the approach implemented in this study and they lUnher prove toot the optimized Fuzzy Logic Controller is functioning better than the conventional PID Controller